True detectives : [compact disc, unabridged] : a novel - Kellerman, Jonathan (Kellerman, Jonathan. Alex Delaware novels., 2009)
Bound by blood but divided by troubles, Moses Reed, a no-frills LAPD detective, and Aaron Fox, ex-cop turned high-end private eye, usually go their separate ways. But the disappearance of Caitlin Frostig isn't usual. A straight-A student from Malibu, Caitlin has only two men in her life: her sullen single father and her wholesome college sweetheart. Reluctantly tag-teaming in a search for fresh leads, Moses and Aaron uncover more than just a secret as they descend into the sinister, seamy side of the City of Angels after dark.